2017
DOI: 10.1002/dys.1558
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and Non‐verbal Fluency in Adults with Developmental Dyslexia: Phonological Processing or Executive Control Problems?

Abstract: The executive function of fluency describes the ability to generate items according to specific rules. Production of words beginning with a certain letter (phonemic fluency) is impaired in dyslexia, while generation of words belonging to a certain semantic category (semantic fluency) is typically unimpaired. However, in dyslexia, verbal fluency has generally been studied only in terms of overall words produced. Furthermore, performance of adults with dyslexia on non-verbal design fluency tasks has not been exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 63 publications
3
29
2
2
Order By: Relevance
“…Our findings of impaired verbal fluency in the DD group are in line with some of the earlier studies on this population (Brosnan et al, 2002; Hatcher et al, 2002; Smith-Spark et al, 2017; Snowling et al, 1997). A plausible explanation for the generally poorer verbal fluency performance in the DD group is that it reflects impaired frontally regulated executive control (Pennington, 2006; Pennington & Bishop, 2009), general lexical retrieval difficulties (Nation, 2005; Nation, Marshall, & Snowling, 2001; Ullman & Pierpoint, 2005), or impaired speed of processing (McDowd et al, 2011; McGrath et al, 2011; Willcutt et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings of impaired verbal fluency in the DD group are in line with some of the earlier studies on this population (Brosnan et al, 2002; Hatcher et al, 2002; Smith-Spark et al, 2017; Snowling et al, 1997). A plausible explanation for the generally poorer verbal fluency performance in the DD group is that it reflects impaired frontally regulated executive control (Pennington, 2006; Pennington & Bishop, 2009), general lexical retrieval difficulties (Nation, 2005; Nation, Marshall, & Snowling, 2001; Ullman & Pierpoint, 2005), or impaired speed of processing (McDowd et al, 2011; McGrath et al, 2011; Willcutt et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…It was further hypothesized that the three tasks would correlate weakly to moderately with each other, reflecting partly overlapping and partly unique neurocognitive mechanisms. Due to the assumed greater dependence on phonological skills, letter fluency was expected to correlate more strongly with phonological awareness and RAN, compared to both semantic fluency and action fluency (e.g., Smith-Spark et al, 2017). The results, which partly confirmed our hypotheses, are discussed below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goddard et al (2014) also reported category fluency to be a significant predictor of autobiographical memory in children with autism. Although measures of verbal fluency are often considered to reflect executive functioning (Pennington & Ozonoff, 1996;Smith-Spark, Henry, Messer, & Ziecik, 2017), there is evidence that they may be more strongly related to language ability (e.g. Henry, Messer, & Nash, 2015).…”
Section: Languagementioning
confidence: 99%
“…Given that phonemic fluency is an area in which adults with dyslexia have been found to have difficulties (e.g., Brosnan et al, 2002;Smith-Spark, Henry, Messer & Zięcik, 2017), it may well be that at least some of the PM difficulties experienced by people with dyslexia are related to this area of executive functioning and, more particularly, the efficient and flexible access of information in verbal long-term memory (Fisk & Sharp, 2004). Although the argument is more than a little tenuous at present, verbal fluency may provide a link between the contributions of executive functioning deficits and the retrospective memory difficulties considered previously in this section (see also Smith-Spark, Moss et al, 2016).…”
Section: Difficulties With the Prospective Component Of Pmmentioning
confidence: 99%